TYPE OF STUDY PROGRAM AND LANGUAGE LEARNING STRATEGIES OF UNIVERSITY STUDENTS: A CASE IN THE NORTHEAST OF THAILAND - Toomnan, Parichart (PEOPLE: International Journal of Social Sciences, 2019)
The objectives of this research work were to scrutinize the frequency of undergraduates’ use of Language learning strategies (LLSs) and to examine whether the selections of LLSs vary greatly in relation to students’ study program types and the patterns of significant variations, if they exist at all. Subjects for the present study were 579 students. Language Learning Strategy Questionnaire (LLSQ) was used to assemble data. Descriptive statistics, ANOVA, and Chi-Square Tests were employed to analyze the obtained data. The results of this study provided LLS usage of undergraduates were identified as moderate frequency level. It was found that students’ type of study program had effects on their choices of LLSs. Non-English Education undergraduates tended to use strategies significantly more frequently than English Education undergraduates. For category level, it was found that significant variations were found in Prep and Under categories.